2007
DOI: 10.1021/jf070953h
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Perchlorate Exposure in Milk from Concentrations in Dairy Feed

Abstract: Perchlorate has been detected in U.S. milk samples from many different states. Applying data from a recently reported 9-week experiment in which 16 Holstein dairy cows were administered perchlorate allowed us to derive an equation for the dose-response relationship between perchlorate concentrations in feed/drinking water and its appearance in milk. Examination of background concentrations of perchlorate in the total mixed ration (TMR) fed in addition to the variable dose supplied to treated cows as a ruminal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 15 publications
2
10
3
Order By: Relevance
“…18,21,43,44 Perchlorate can bioaccumulate in milk because perchlorate absorbed from consumption of forage crops is actively transported during lactation by the sodium-iodide symporter present in the mammary gland. 17,26,30,[45][46][47] The adolescent and adult food models also show that consumption of vegetables and fruits were significant sources of perchlorate, which is consistent with earlier studies. 21,22,44 In addition, the contribution of dark-green leafy vegetables, which was significant in the adult food model, is well-supported by other studies.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…18,21,43,44 Perchlorate can bioaccumulate in milk because perchlorate absorbed from consumption of forage crops is actively transported during lactation by the sodium-iodide symporter present in the mammary gland. 17,26,30,[45][46][47] The adolescent and adult food models also show that consumption of vegetables and fruits were significant sources of perchlorate, which is consistent with earlier studies. 21,22,44 In addition, the contribution of dark-green leafy vegetables, which was significant in the adult food model, is well-supported by other studies.…”
Section: Discussionsupporting
confidence: 89%
“…13 The presence of perchlorate in the environment leads to contamination in certain types of foods. 11,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] The Food and Drug Administration (FDA) Total Diet Study in 2005-2006 found perchlorate in numerous food groups: dairy products, fruits, and vegetables were identified as the primary sources of perchlorate exposure. 21 Other studies have also found perchlorate in fruits and vegetables 11,16,17,19,[22][23][24][25]27,31 and dairy products.…”
Section: Introductionmentioning
confidence: 99%
“…This contamination can arise from natural sources (Rajagopalan et al, 2006;Rao et al, 2007), diffuse releases from fertilizer use (Dasgupta et al, 2006;Rice et al, 2007), and localized contamination from explosives and fireworks (MDEP, 2006). Jackson et al (2004) found groundwater perchlorate concentrations greater than 0.5 mg/l in 46% of wells in west Texas and New Mexico.…”
Section: Perchlorate Concentrations In Drinking Watermentioning
confidence: 99%
“…Rajagopalan et al (2006), sampling in the same area, reported groundwater perchlorate concentrations between 0.1 mg/l and 4 mg/l in 35% of wells. Data from Massachusetts (MDEP, 2006) and Maryland (Rice et al, 2007), as well as infrequent detections in the UMCR1 data for many states at locations distant from known perchlorate releases, likewise suggest that low-level perchlorate contamination may be common, if not ubiquitous, in drinking water.…”
Section: Perchlorate Concentrations In Drinking Watermentioning
confidence: 99%
“…Dairy products have been associated with human exposure to perchlorate (Rice et al 2007), and infants, in particular, can be exposed to perchlorate through bovine milk, human breast-milk (Gindberg et al 2007; Rice et al 2007), and infant formula (Schier et al 2010). Kirk et al (2003, 2005) reported the presence of perchlorate in all 47 dairy milk samples collected from 11 states and in 35 of 36 human milk samples collected from 18 states in United States.…”
Section: Introductionmentioning
confidence: 99%